Prevalence and predictors of HIV infection among adults aged 50 years and above in Shinyanga, Iringa and Ruvuma regions of Tanzania - Ezekiel, Mangi; E. Matemba, Lucas; Mosha, Idda; Nyamhagatta, Mukome; Lwezaura, Sharon; Moshiro, Candida (International Journal of Scientific Research and Management (IJSRM), 2020)
Background The UNAIDS Report on the global AIDS report show  that 35.3 million people living with HIV globally, out of that an estimated 3.6 million are people aged 50 years or above.MethodsThis was a cross sectional study conducted in Shinyanga, Iringa and Ruvuma regions in Tanzania aiming at determining prevalence and risk factors for HIV infection among elderly people aged 50 years and above. Random sampling was employed to select 2,214 participants. HIV testing to consenting participants was conducted and a survey was used to collect data on socio-demographic information, medical conditions and sexual behavioral factors. ResultsThe overall prevalence of HIV infection among study participants was 4.4% (95% CI=3.6-5.4). The prevalence was higher among females compared to males. Majority of study participants were aware of HIV, transmission and preventive measures. Few respondents knew that a person could be infected through anal sex. More than half of the participants prefer HIV status to remain confidential. A significantly larger proportion (24.2%) of males reported to ever use a condom during their last sexual intercourse compared to females (9.5%). Compared to older age groups, respondents aged 50-59 years were significantly more likely to report condom use during last sexual intercourse. Being in the fourth of highest wealth quintile, ever use of condom, condom use during last sexual encounter, having 2 or more partners in the last one year were associated with an increased risk of HIV infection.ConclusionThe high prevalence of HIV among study participants highlights the prerequisite for increased attention to address underlying risk factors for HIV infection among adults.